Paul's View of Israel's Misstep in Rom 9.32-3: Its Origin and Meaning - Thielman, Frank (New Testament studies, 2018)
The form of Paul's citation of Isa 28.16 and 8.14 in Rom 9.32-3 indicates not only that his source was an early Christian collection of stone texts but also that this collection followed a particular interpretation of Jesus' death: Jerusalem's ruling class planned Jesus' death because of his controversial approach to the law and the temple. Paul quotes these texts to help explain why unbelieving Israel has rejected the gospel. Like Israel's ruling elites, they have lost sight of the law's weightier matters. Punctuated correctly, 1 Thess 2.14-16 confirms this understanding of Rom 9.32-3.